Opportunities for performance improvement in relation to medication administration during pediatric stabilization. Issue 3 (2nd June 2006) - Morgan, N; Luo, X; Fortner, C; Frush, K
Abstract : Objectives: To identify and characterize areas for improvement in the clinical performance of nurses in relation to medication administration. Method: Nurses participated in a simulated pediatric stabilization event which was videotaped. Their clinical performance was evaluated at each of the following steps: (1) communicating and confirming the dose of medication; (2) converting the dose; (3) selecting the correct medications; (4) properly preparing the medication formulation; and (5) measuring medication doses. The time required to convert and draw up the medications was also evaluated. Results: A total of 150 medication orders for five medications were given by the physician. Only 55% of the orders were verbally repeated back by the nurses. Of the 120 orders in which the doses were converted from milligrams to milliliters by nurses, 17 (14.2%) were converted incorrectly and the maximum dose deviation reached 400%. Selection of the wrong medication occurred in 11 of the 150 orders. Dextrose (which requires dilution before being administered to children) was not diluted in 17% of the medication orders and in 12% it was diluted improperly. About 40% of the orders for ceftriaxone (which requires reconstitution) were not properly reconstituted. In 49 (32.7%) of the 150 medication orders that were drawn up in a syringe, the amount measured was not consistent with the stated dose. For some medications, a prolonged time was required by nurses to convert the doses and draw up the medications. Conclusions: By observing the clinical performance of nurses in a simulated videotaped pediatric stabilization event, we have identified some important areas in need of improvement in each step of the medication administration process. These findings indicate a need for improved education, training, and use of clinical aids or adjuncts for pediatric emergency nurses.